1995
DOI: 10.1017/s0890037x0002426x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Imazethapyr and Paraquat-Based Weed Control Systems in Peanut (Arachis hypogaea)

Abstract: Field studies were conducted from 1991 through 1993 to compare Weed control, peanut tolerance, yield, and net return from imazethapyr applied alone or in combination with paraquat. Sicklepod and Florida beggarweed were controlled with paraquat early POST followed by a POST application of either paraquat with 2,4-DB or paraquat with 2,4-DB and bentazon. Imazethapyr-based early POST treatments offered no improvement. An early POST application of paraquat with bentazon or imazethapyr was required for maximum cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Including acifluorfen plus bentazon in the tankmixture resulted in a reduction in injury when compared to paraquat alone. Similar results were noted by Grey at al. (1995).…”
Section: Non-irrigated Studysupporting
confidence: 92%
See 1 more Smart Citation
“…Including acifluorfen plus bentazon in the tankmixture resulted in a reduction in injury when compared to paraquat alone. Similar results were noted by Grey at al. (1995).…”
Section: Non-irrigated Studysupporting
confidence: 92%
“…containing paraquat reduced visible injury to the peanut crop similar to previous research (Grey et al, 1995;Wehtje et al, 1992). Grade variation was due to cultivar differences for both the irrigated and non-irrigated studies.…”
Section: Discussionsupporting
confidence: 78%
“…must occur with the addition of other herbicides such as imazethapyr and imazapic (Cole et al, 1989, Grey et al, 1995, Wilcut et al, 1991a, 1994c. Imazethapyr applied postemergence (POST) provided broad-spectrum and most consistent control when applied within 10 d of weed emergence (Cole et al, 1989;Grey et al, 1995;Grichar et al, 1992;Wilcut et al 1991a, b;1994b, c). Imazapic applied POST controls the same spectrum of weeds as imazethapyr (Nester and Grichar, 1993;Grichar et al, 1994;Wilcut et al, 1993Wilcut et al, , 1994cWilcut et al, , 1995 (Grey et al, 2001).…”
mentioning
confidence: 99%
“…Imazethapyr can be applied either preplant incorporated, preemergence, or postemergence (Wilcutei al, 1991a,b;1994a,b). Grey et al (1995) reported that tank-mixed combinations of paraquat and imazethapyr applied early postemergence, followed by various other treatments, generally resulted in optimum net returns. Conversely, systems in which imazethapyr was applied alone generally had lower eco nomic returns.…”
mentioning
confidence: 99%